Penatalaksanaan Holistik Pada Pasien TBC Milier – HIV Seronegatif - Annisa Abdillah; Azelia Nusadewiarti (CV. Jasa Sukses Abadi, 2019)
Miliary TBC is a potentially fatal form of TBC. Mortality rates for military TBC occurs higher in adults (25% - 30%) than in children (15% - 20%). Clinical manifestations of patients with miliary tuberculosis in adults are not specific. Therapy is given not only by using drugs, but also the therapy should be focus on the patient or patient-centered and family approach which is done holistically. The study is Case Report. Primary data was obtained through history taking and physical examination by making home visits, filling out family folders, and filling in patient files. Assessment was carried out based on the initial holistic diagnosis, process, and end of the visit quantitatively and qualitatively. Based on holistic diagnosis, the patient complains fever for 6 months, accompanied by night sweats, decrease appetite, nausea, weight loss. The patient is worried that his pain will become increasingly burdensome and life threatening. The patient is a man, 53 years. Patients have fungtional degrees 2 with Milliary TBC – HIV Seronegative, have internal risk factors, such as drinking alcohol and smoking habits, curative treatment patterns, rarely exercise and lack of knowledge about the disease. The intervention and evaluation has been done to the patient and his family members about patient’s illness, medications, lifestyles, obtained changes in the behavior of patients and families. The diagnosis of milliary tuberculosis in this cases is in accordance with the theory and critical appraisal of resent research.